Synthesis and anion recognition studies of new ureylbenzamide-based receptors - Moreno Valle, Bibiana; Aguilar Martínez, Milagros; Ocho-Terán, Adrián; Martinez Quiroz, Marisela; Miranda Soto, Valentín; García Elias, José; Ochoa Lara, Karen; Labastida Galván, Victoria; Ordoñez, Mario (My University, 2017)
A new group of ureylbenzamide-based receptors (1–4) has been synthesized; its binding affinity and capacity to form supramolecular complexes in solution with different anions have been investigated. For designing these receptors, it was considered a combination of the positions of the urea and amide groups (ortho and meta), and the chromophore groups naphthyl and nitrophenyl, yielding four receptors. The position and chromophore structure affected the acidity of the urea and amide hydrogens in the order 4>3>2>1. All the spectroscopic studies showed a significant change of 1 and 2 compared with 3 and 4 in the presence of different TBAX salts in acetonitrile. The 1H-NMR spectra show a preferential interaction of the anions with the urea group in receptors 1 and 2 due to the less steric hindrance, while there is a cooperative interaction of amide group in receptors 3 and 4 due to the closeness of both groups.
Journal Supramolecular Chemistry
Keywords: Anion recognition; Urea; Benzamide; Receptor; Sistemas